PERSEPSI MAHASISWA KEDOKTERAN TERHADAP PEMBELAJARAN ANATOMI DAN HISTOLOGI DI ERA PENDIDIKAN MEDIS MODERN - Anugrah Ramadhan (Jurnal Medika Hutama, 2026)
Background: Anatomy and histology are fundamental components of medical education; however, students frequently perceive these subjects as difficult and heavily reliant on memorization. The increasing use of digital learning tools, including virtual microscopy (VM) and three-dimensional (3D) anatomical models, offers new opportunities to enhance student engagement and conceptual understanding. Objectives: This study aimed to describe medical students’ perceptions of anatomy and histology learning in the context of modern medical education and to identify potential implications for curriculum improvement. Methods: A descriptive cross-sectional study was conducted among 341 undergraduate medical students. Data were collected using a validated structured questionnaire distributed via Google Forms. Descriptive statistical analysis was performed to summarize students’ perceptions of anatomy and histology learning. Results: Most students reported positive perceptions of anatomy (97.9%) and histology (94.4%) learning, predominantly within the “good” and “very good” categories. Female students constituted the majority of respondents (82.1%), and most participants were aged 20–21 years. The findings indicate that learning strategies integrating clinical relevance and digital educational tools were perceived as effective in supporting student understanding. Conclusion: Medical students demonstrated predominantly positive perceptions of anatomy and histology learning, reflecting the effective implementation of clinically integrated and technology-enhanced teaching approaches. Continuous student feedback, balanced blended learning models, and ongoing faculty development are recommended to maintain and further improve the quality of undergraduate medical education.